Навчально-методичний комплекс для підготовки майбутніх офіцерів запасу у закладах вищої освіти - Зорій, Ярослав (My University, 2018)
У статті розглядається проблема формування готовності майбутніх офіцерів запасу до ефективної військово-професійної діяльності під час навчання у військових закладах вищої освіти (військових навчальних підрозділах закладів вищої освіти), а також важливість використання в освітньому процесі «навчально-методичного комплексу» як однієї з основних умов забезпечення якості військової підготовки. One of the main characteristics of an officer’s preparedness for his professional activity is developing his capability in critical and creative thinking as they learn to generate and evaluate knowledge and clarify concepts of military professionalism. Without profound knowledge, versatile skills, without initiative, creativity training as core constructs of professional preparedness those ongoing transformations in military affairs are impossible. Consequently, the Higher Education Institutions’ Reserve Officers Training Corps programs involve, at their core, an ability to respond effectively to new requirements for professional defense of the nation as well as his establishing as a personality in general and his readiness for military-professionalism in particular. Prior research has suggested that the concept of ‘ preparedness’ by capacity and competence as well as its treatment, and argues that the concept of ‘attitude’ can be understood as an agile, integrated, selective readiness of the individual to come into contact with various parties of reality, including the military one. To all concerned, it means preparing individuals from a civilian society to perform as professional military personnel. The rapid changes in technology, tactics, and missions that are characteristic of today’s military operations require matching agility in the design and development of training and education programs. These changes must be made quickly and efficiently. Among these reasons are those that stem from the magnitude of military research and development in training, specific products of military training, practices for designing and developing military training, and procedures for assessing military training programs, especially those concerned with cost and effectiveness. What is demonstrated many military training programs, packages, simulations, and other materials prepared for military training could find direct application in the civilian sector. There has been considerable interest in adapting military training packages for application in civilian education and training institutions. Most evaluations of new instructional approaches are performed by instructional researchers and innovators who simply want to know if a new approach of military preparedness works.
Keywords: військова підготовка; майбутні офіцери запасу; військово-професійна діяльність; готовність до діяльності; навчально-методичний комплекс